2019
DOI: 10.1097/pq9.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a Virtual Fracture Clinic Increases Efficiency and Reduces Costs in Torus Fracture Management

Abstract: Background: Torus fractures of the distal radius are both a common pediatric forearm fracture and a common source of referral to orthopedic departments. Management of these injuries has moved away from traditional casting methods to using splints and softcasts. Aim: With the recent introduction of a virtual fracture clinic (VFC), we sought to improve our compliance with guidelines while ensuring all patients undergo review in the clinic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…The study was conducted in accordance with the Declaration of Helsinki and was approved by the local ethical committee of OLVG Hospital (ref no 18.071) and by its board of directors.…”
Section: Competing Interests None Declaredmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in accordance with the Declaration of Helsinki and was approved by the local ethical committee of OLVG Hospital (ref no 18.071) and by its board of directors.…”
Section: Competing Interests None Declaredmentioning
confidence: 99%
“…7 DD has been studied for several SSIs within the United Kingdom (UK), including, among others, Mason type 1 radial head fractures, 8 9 fifth metacarpal neck fractures, 8 10 11 base of fifth metatarsal fractures, 8 12 13 buckle-type fractures of the distal radius, and pediatric clavicle fractures. [14][15][16][17][18] These studies indicate that DD reduces follow-up appointments, imaging, no-shows, and costs without compromising outcome and experience. To our knowledge, however, no studies have been performed outside the UK, whereas it is important to externally validate and evaluate effects in other settings, such as a different country.…”
Section: Introductionmentioning
confidence: 99%
“…63 A recent retrospective study also demonstrated increased efficiency and cost reduction in managing these injuries in a VFC setting. 21 …”
Section: Paediatric Injuriesmentioning
confidence: 99%
“…However, previous studies on VFCs have shown their effectiveness for the management of a number of orthopaedic injuries not requiring surgical intervention. These include patients with simple radial head fractures, little finger metacarpal fractures, fifth metatarsal fractures, and buckle fractures in children [ 20 , 21 ]. Bhattacharya et al found that patients with undisplaced clavicle fractures can be discharged after a single virtual consultation with good patient outcomes and satisfaction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%